Podtalnica Ljubljanskega polja - Rejec Brancelj, Irena; Kladnik, Drago; Smrekar, Aleš (Geografija Slovenije, 2005)
Ljubljansko polje is a juncture of numerous human activities. The source of drinking water for about 300,000 residents, it holds one of the most important bodies of groundwater in the country. Unfortunately, the influences of urbanization, agriculture and industry that threaten and burden it are reflected in the quality and quantity of the groundwater.